La conciencia psicológica en la enseñanza y la práctica espiritual y religiosa - Pimentel Martínez, Josefina ('Ilu. Revista de Ciencias de las Religiones, 2010)
The objective of this research is to explore and describe the psychological elements of education and spiritual and religious practice of the respondents objectified in beliefs and attitudes in daily life.
Keywords: Religion; Psychology; Social work